PCR-based Detection and Prevalence of Theileria Species in Sheep from Quetta District, Balochistan - Tariq, Nabeela; Khan, Maria; Shaikh, Tahreem; Zil e Huma; Shakeela daud (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Background: Theileriosis is a serious hemoparasitic illness that severely limits the production of small ruminants. The current study aims for early and accurate detection of theileriosis using polymerase chain reaction for treatment as conventional techniques are not specific. Blood samples were collected from sheep between July and October of the year 2020. A total of 100 samples were taken, 69 samples were from tick-infested sheep exhibiting illness signs, while 31 samples were from tick-free sheep. To detect Theileria species in sheep, DNA was extracted, and the PCR method was used. The prevalence of T. lestoquardi and T. ovis was 22.47% and 64.04%, respectively, with a 13.48% frequency of mixed infection with both species. T. ovis was detected in around 80% of tick-infested sheep, indicating a significant association (P < 0.01) with ticks. T. lestoquardi was found in 28.99% of tick-infested sheep, indicating a significant connection (P < 0.001) with ticks. The incidence of T. ovis was significantly related to the summer season but T. lestoquardi was non-significantly related to the summer season (P > 0.05). A high prevalence of Theileriosis is found in Quetta. The parameters studied were strongly correlated to the infection except for T. lestoquardi with the summer season. Early detection with the help of polymerase chain reaction can accelerate treatment and reduce transmission to increase livestock production in Pakistan.